Peran Account Payable terhadap Kelancaran Pembayaran Tagihan Supplier di Pesonna Tugu Hotel Yogyakarta - Riskiani, Nita; Putri, Emmita Devi Hari (Sekolah Tinggi Pariwisata AMPTA, 2019)
The results of this study were to analyze the supplier bill payment process at Pesonna Tugu Hotel Yogyakarta, among others, suppliers exchanging receipts, making payment vouchers, sending memos, and overbooking processes. The process of paying supplier bills for obstacles includes suppliers being late in exchanging receipts, purchasing and receiving late submitting documents and not being complete, sending late memos and late overbooking processes. Accounts Payable overcome obstacles by contacting suppliers to immediately exchange receipts, remind purchasing and receiving to immediately deposit documents, process the sending of memos at the end of the month, and remind PT Pesonna Indonesia Jaya to immediately overbooking. The role and responsibility of account payable is very important in the process of payment of supplier bills, so that the account payable goes smoothly, then the account payable must establish good communication with suppliers, purchasing, and receiving.